A new species of Stenolemus Signoret (Hemiptera: Heteroptera: Reduviidae: Emesinae) from India - Mukherjee, Paramita; Ambrose, Dunston P.; Hassan, M. E.; Biswas, B. (Zootaxa, 2015)
A new species of Stenolemus Signoret, 1858, Stenolemus annulatus sp. nov. (Reduviidae: Emesinae) is described from India. This new species is closely related to S. susainathani Wygodzinsky from Nilgiri Hills, South India and S. larat Wygodzinsky from Moluccas, Larat, by sharing common characteristics such as the ratio of distance between eyes and their width, long antennal first segment, slightly elevated postocular region of head and sharply divided pronotum into three parts, but can be easily separated by the following diagnostic characteristics: pronotum with petiole about as long as forelobe and 1.3 times shorter than hindlobe, first antennal segment with five annulations, rostrum creamy white and luteous at apex, basal and lateral areas of second segment; hind lobe of pronotum with 1+1 submedian conical rounded projections; forecoxa shorter than hind lobe of pronotum, foretibia with one subbasal and one submedian annulation and hind femora reaching apex of forewings. A key to Indian species of the genus Stenolemus is given.